STEM Club Participation and STEM Schooling Outcomes - Michael A Gottfried; Darryl Williams (Arizona State University, 2013)
To develop a more robust understanding of the relationship between non-formal, school-based STEM activities and students' success and persistence in STEM fields, this study evaluates how math club participation influences math GPA and how science club participation influences science GPA. Additionally, this study evaluates how math or science club participation associates with the probability of selecting a STEM major in college. Utilizing data from the National Longitudinal Study of Adolescent Health (Add Health) to examine these relationships, the results suggest that there is a STEM achievement gap in the success and persistence of students who do and do not participate in STEM-related extracurricular clubs. While, for the most part, the results were not differentiated by gender or race/ethnicity per se, they were in fact distinguishable by poverty status and the interaction between race and poverty status.